A high-light-efficiency pure red light quasi-two-dimensional perovskite film and its preparation method and application
By controlling the concentration of crown ether solvents and antisolvents and the heat treatment process, the growth and crystallization process of perovskite films is regulated, and the problem of unstable emission of pure red light in the existing technology is solved, achieving high-light efficiency and accurate pure red light Emission and wide color gamut effects are suitable for the preparation of fluorescent anti-counterfeiting films.
Patent Information
- Application Number
- CN202411375525.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-30
AI Technical Summary
The prior art is difficult to achieve pure red light emission that meets the Rec. 2020 standard, and the phase distribution and energy funnel effect of the quasi-two-dimensional perovskite film are difficult to control, resulting in a light emission wavelength greater than 640 nm, making it difficult to obtain efficient and stable pure red light emission. .
By controlling the concentration and addition amount of crown ether solvents and anti-solvents, the PPA2CsPb2I7 substrate is subjected to directional regulation, combined with heat treatment technology, the film growth and crystallization process is regulated, the phase distribution of multiple quantum wells is reduced, and pure red light emission is achieved.
It achieves high-light efficiency pure red light emission, accurate emission wavelength and narrow peak width, complies with the requirements of Rec. 2020, and facilitates the continuous production of large-area centimeter-level quasi-two-dimensional perovskite films, and is used to prepare fluorescent anti-counterfeiting films.
Smart Images

Figure CN118880430B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a pure red light perovskite film, in particular to a high-light-efficiency pure red light quasi-two-dimensional perovskite film and a preparation method and application thereof, belonging to the technical field of perovskite materials. Background Art
[0002] In the context of the digital and information age, display technology has been widely and deeply integrated into many scenarios, such as smartphones, tablets and large outdoor displays. However, with the improvement of living standards, people's demand for high-quality displays continues to increase. One of the keys to achieving ultra-high-definition display is to develop luminescent materials with a wide color gamut. To meet this demand, one of the keys is to continuously improve the color gamut range of luminescent materials for display. Among them, the development and design of materials with pure red light emission is one of the keys. In this regard, the International Telecommunication Union proposed the Rec. 2020 standard, which stipulates that the luminescent peak of pure red light should fall at 630 nm, and the half-peak width of the luminescent spectrum should be as small as possible. In other words, the closer the luminescent wavelength of the red light luminescent material is to 630nm, and the smaller the half-peak width of its luminescent spectrum, the wider the corresponding color gamut range and the clearer the display.
[0003] Metal halide perovskite has the advantages of high fluorescence quantum efficiency, narrow half-width, continuously tunable band gap, and simple preparation method. It is an ideal new type of light-emitting material for display. In order to obtain pure red light that meets the Rec. 2020 standard, it is generally necessary to construct a perovskite with a suitable band gap. At present, there are three main methods to achieve pure red light emission from metal halide perovskites. The first is based on mixed halogen perovskites, using bromine-iodine alloying to regulate the band gap of CsPbI3 perovskite to achieve pure red light emission. However, the mixing of halogens can easily cause ion migration, resulting in unstable luminescence spectrum of perovskite, limiting its further application. In order to effectively avoid the problem of ion migration, the other two strategies are based on pure iodine-based perovskites to achieve pure red light emission. Among them, the luminescence peak of tin-based two-dimensional perovskites is easily located in the pure red light region, but its Sn 2+ However, its instability and weak luminescence efficiency have hindered its further application. Lead-based two-dimensional perovskite is a good choice for obtaining efficient and stable pure red light emission. Quasi-two-dimensional perovskite films are often composed of mixed quantum wells of multiple n phases, and perovskites with different emission wavelengths can be obtained by adjusting the thickness of the inorganic layer. Due to the energy funneling effect, the carriers of the quasi-two-dimensional perovskite are easily transferred from the small n phase to the large n phase. In the energy band of the large n phase perovskite with a small band gap, the carriers undergo radiative recombination, and the emission wavelength falls in the deep red or near-infrared region. For this reason, it is very challenging to design efficient and stable pure red light quasi-two-dimensional perovskites.
[0004] Most of the lead-based two-dimensional red-light perovskites reported so far have PL emission wavelengths greater than 640 nm. There are few reports of pure red-light quasi-two-dimensional perovskites that meet the requirements of Rec.2020. The difficulty lies in the difficulty in controlling the phase distribution and energy funneling effect of perovskite films. Summary of the invention
[0005] In view of the problems existing in the prior art, the first purpose of the present invention is to provide a high-light-efficiency pure red light quasi-two-dimensional perovskite film. The film is based on the synergistic effect between the components. By controlling the concentration and addition amount of crown ether solvents and anti-solvents, the PPA2CsPb2I7 substrate is directionally regulated, and then combined with a heat treatment process, the film growth and crystallization process is regulated, and the phase distribution of its multiple quantum wells is reduced, thereby obtaining a perovskite film emitting pure red light.
[0006] The second object of the present invention is to provide a method for preparing a high-light-efficiency pure red light quasi-two-dimensional perovskite film. The method has the advantages of simple process, easy operation and low cost, and the crystal precipitation process and the subsequent heat treatment process are carried out in the same equipment, which is convenient for realizing the continuous production of large-area centimeter-level quasi-two-dimensional perovskite films.
[0007] The third object of the present invention is to provide an application of a high-light-efficiency pure red light quasi-two-dimensional perovskite film for preparing a fluorescent anti-counterfeiting film. The quasi-two-dimensional perovskite film provided by the present invention has the advantages of precise luminous wavelength and narrow peak width, and achieves the technical effect of high red light emission purity and wide color gamut of the perovskite film; the fluorescent anti-counterfeiting film prepared based on the above quasi-two-dimensional perovskite film has the advantages of high luminous brightness and good air stability, which meets the requirements of Rec.2020.
[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing a high-light-efficiency pure red light quasi-two-dimensional perovskite film, wherein raw materials including phenylpropylamine iodide, cesium iodide and lead iodide are fully dispersed in a solvent, and then a crown ether solution is added to obtain a film precursor solution, and then the film precursor solution is placed on a clean substrate for crystal precipitation and heat treatment in sequence to obtain;
[0009] The stoichiometric ratio of the phenylpropylammonium iodide, cesium iodide and lead iodide is 2:1-2:2; the mass molar ratio of the crown ether solution to the phenylpropylammonium iodide is 1:0.8-1.2 g / mol based on the mass of the solute;
[0010] An anti-solvent may be added during the crystal precipitation process; the anti-solvent is at least one of chlorobenzene, benzene, methanol and dichloromethane;
[0011] The chemical formula of the two-dimensional perovskite film is PPA2CsPb2I7, where PPA=C9H 14 N.
[0012] As a preferred solution, the solvent is at least one of N,N-dimethylformamide, dimethyl sulfoxide, and acetonitrile.
[0013] As a preferred solution, the concentration of iodide in the thin film precursor solution is 0.01-0.08 mol / L.
[0014] As a preferred solution, the concentration of the crown ether solution is 5-20 mg / L.
[0015] As a preferred solution, the crown ether solution is at least one of 18-crown ether-6 solution, 15-crown ether-5 solution and dicyclohexane-18-crown ether-6.
[0016] As a preferred solution, the cleaning process of the clean substrate is: ultrasonically cleaning the substrate with acetone, isopropanol, detergent, deionized water, acetone and isopropanol in sequence, then blowing dry the surface liquid phase on the substrate with nitrogen, and then drying at a temperature of 40-80°C until completely dry.
[0017] As a preferred solution, the precursor solution and the clean substrate need to be preheated before the crystals are precipitated, and the conditions are: the preheating temperature is 60-120° C. and the time is 2-10 minutes.
[0018] As a preferred solution, the conditions for crystal precipitation are: temperature of 80-120° C. and time of 1-5 min.
[0019] As a preferred solution, the heat treatment conditions are: temperature of 80-120° C. and time of 15-30 min.
[0020] As a preferred solution, the volume ratio of the anti-solvent to the precursor solution is 1-3:1-4.
[0021] The present invention also provides an application of a high-light-efficiency pure red-light quasi-two-dimensional perovskite film prepared by the above method, which is used for preparing a fluorescent anti-counterfeiting film.
[0022] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are:
[0023] 1) The quasi-two-dimensional perovskite film provided by the present invention is based on the synergistic effect between the various components. By controlling the concentration and addition amount of the crown ether solvent and the anti-solvent, the PPA2CsPb2I7 substrate is directionally regulated, and then combined with the heat treatment process, the film growth crystallization process is regulated, and the phase distribution of its multiple quantum wells is reduced, thereby obtaining a perovskite film with pure red light emission.
[0024] 2) The preparation method provided by the present invention has the advantages of simple process, easy operation and low cost, and the crystal precipitation process and the subsequent heat treatment process are carried out in the same equipment, which is convenient for realizing the continuous production of large-area centimeter-level quasi-two-dimensional perovskite films.
[0025] 3) In the technical solution provided by the present invention, the quasi-two-dimensional perovskite film provided by the present invention has the advantages of precise luminescent wavelength and narrow peak width, which achieves the technical effect of high red light emission purity and wide color gamut of the perovskite film; the fluorescent anti-counterfeiting film prepared based on the above-mentioned quasi-two-dimensional perovskite film has the advantages of high luminescent brightness and good air stability, which meets the requirements of Rec.2020. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The photoluminescence spectra of the PPA2CsPb2I7 thin film samples prepared in Example 1 and Comparative Example 1 and the pictures of the two under 365 nm ultraviolet light;
[0027] Figure 2 It is the infrared spectra of the PPA2CsPb2I7 thin film samples prepared in Example 1 and Comparative Example 1;
[0028] Figure 3 It is the X-ray photoelectron spectrum of the PPA2CsPb2I7 thin film samples prepared in Example 1 and Comparative Example 1;
[0029] Figure 4 is a scanning electron microscope image of the PPA2CsPb2I7 thin film samples prepared in Example 2 and Example 3;
[0030] in, Figure 4 (a) is a scanning electron microscope image of the PPA2CsPb2I7 thin film sample prepared in Example 2. Figure 4 (b) is a scanning electron microscope image of the PPA2CsPb2I7 thin film sample prepared in Example 3;
[0031] Figure 5 is the slightly incident XRD pattern of the PPA2CsPb2I7 thin film samples prepared in Example 2 and Example 3;
[0032] Figure 6 is the photoluminescence spectrum of the PPA2CsPb2I7 thin film samples prepared in Example 2 and Example 3;
[0033] in, Figure 6 (a) is the photoluminescence spectrum of the PPA2CsPb2I7 thin film sample prepared in Example 2 of the present invention, Figure 6 (b) is the photoluminescence spectrum of the PPA2CsPb2I7 thin film sample prepared in Example 3 of the present invention;
[0034] Figure 7 is an image of a patterned QR code of a PPA2CsPb2I7 thin film prepared in Example 4;
[0035] in, Figure 7 (a) is the image of the QR code under natural light. Figure 7 (b) is a photo taken under 365 nm ultraviolet light. DETAILED DESCRIPTION
[0036] The following examples are intended to further illustrate the present invention, but are not intended to limit the present invention. Corresponding adjustments and improvements made without departing from the concept of the present invention all fall within the scope of protection of the present invention.
[0037] Example 1
[0038] 1) Clean the quartz substrate (2.2 cm × 2.2 cm) by ultrasonicating it with acetone, isopropanol, detergent, deionized water, acetone, and isopropanol for 20 min in sequence, then blow dry the solvent on the surface with N2, and place it in a constant temperature air drying oven at 60 °C for 15 min until it is completely dry;
[0039] 2) Dissolve 0.05 mmol of PPAI, 0.025 mmol of CsI, and 0.05 mmol of PbI2 in 1 mL of DMF solvent, add 10 μL of 5 mg / mL 18-crown ether-6 additive, and stir magnetically at 800 rpm for 120 min at 50 °C to obtain a clear precursor solution;
[0040] 3) Preheat the precursor solution and the quartz substrate at 80 °C for about 5 min, take 10 μL of the precursor solution and drop it on the quartz substrate. After about 5 min, the film is completely precipitated. Keep it at this temperature for about 15 min to obtain the 18-crown ether-6 optimized PPA2CsPb2I7 film. The luminescence spectrum and luminescence color electronic photos of the corresponding samples are shown in Figure 1 The emission peak is located at 628 nm, the half-peak width is 55.2 nm, and it emits red light under 365 nm ultraviolet light.
[0041] Comparative Example 1
[0042] This comparative example is completely consistent with Example 1, except that: when preparing the precursor solution, no 18-crown ether-6 additive is added.
[0043] The sample obtained in this comparative example emits weak orange-yellow light under 365 nm ultraviolet light. Different from the luminescence spectrum of the sample in Example 1, the sample in Comparative Example 1 has a double emission peak, with emission peaks at 560 nm and 602 nm respectively; in addition, the luminescence intensity of Comparative Example 1 is weakened by about one order of magnitude, which indicates that the introduction of surface 18-crown ether-6 can effectively reduce the defect density of the perovskite film.
[0044] Figure 2 The Fourier transform infrared spectra of the perovskite film prepared in Example 1 and Comparative Example 1 of the present invention are shown in the figure. As can be seen from the figure, the film after adding crown ether has a peak at 1096 cm -1 Obvious ether bond COC signals appear nearby, indicating that the crown ether has an obvious coordination effect with the film and can effectively passivate defects.
[0045] Figure 3 The X-ray photoelectron spectrum of the perovskite film prepared by combining Example 1 and Comparative Example 1 of the present invention shows that after the crown ether is added, the O 1s binding energy of the obtained sample is significantly enhanced, and the binding energy peak of Pb 4f moves to a lower energy position. This shows that the crown ether and Pb in the perovskite film 2+ It is the active site that coordinates with the crown ether.
[0046] Example 2
[0047] This embodiment is completely consistent with Embodiment 1, except that:
[0048] The precursor solution and the quartz substrate were preheated at 80 °C for about 5 min, 10 μL of the precursor solution was dripped onto the quartz substrate, and then 15 μL of chlorobenzene was immediately dripped. After about 2 min, the film was completely precipitated. The temperature was maintained for about 15 min to obtain the PPA2CsPb2I7 film treated with chlorobenzene. The scanning electron microscopy of the film obtained in this example shows Figure 4 (a).
[0049] Example 3
[0050] This embodiment is completely consistent with Embodiment 1, except that:
[0051] The preheating and heat treatment temperatures were raised to 100 °C. The precursor solution and the quartz substrate were preheated at 100 °C for about 5 min. 10 μL of the precursor solution was dripped onto the quartz substrate, and then 15 μL of chlorobenzene was immediately dripped. After about 1 min, the film was completely precipitated. The temperature was maintained for about 15 min to obtain the PPA2CsPb2I7 film after the optimized annealing temperature. The scanning electron microscopy of the film obtained in this example shows Figure 4 (b).
[0052] Example 4
[0053] This embodiment is completely consistent with Embodiment 3, except that:
[0054] The quartz substrate used was 5 cm × 5 cm. The precursor solution and the quartz substrate were preheated at 50 °C for about 5 minutes. 100 μL of the precursor solution was dropped on the quartz substrate, and then 150 μL of chlorobenzene was immediately added. After about 7 minutes, the film was completely precipitated. The wet film was transferred to a 100 °C heating table and the temperature was maintained at this temperature for about 15 minutes to obtain a uniform centimeter-scale PPA2CsPb2I7 film. A laser with a wavelength of 450 nm, a power of 15 W, and a spot diameter of 0.06 mm was used to finely engrave the two-dimensional code pattern on the film to obtain a patterned sample with fluorescent anti-counterfeiting function. The results are shown in Figure 2. Figure 7 ,pass Figure 7 It can be seen that the obtained QR code pattern is unrecognizable under natural light, but the stored QR code information can be clearly displayed under 365 nm ultraviolet light.
[0055] The present invention also carried out XRD test on the thin film samples obtained in Example 2 and Example 3, and the slightly incident XRD patterns thereof are as follows: Figure 5 As shown in the figure, it can be seen that the samples obtained in Example 2 and Example 3 have highly consistent phase compositions, both of which are multi-quantum well structures composed of multiple n phases, which indicates that the film provided by the present invention has higher sensitivity and higher excitation light efficiency.
[0056] The present invention also conducted a photoluminescence test on the film samples obtained in Example 2 and Example 3, and the spectrum thereof is shown in FIG. Figure 6 As shown in the figure, it can be seen that the emission peak wavelength of the thin film sample obtained in Example 2 is 628.2nm, and the half-width is 49.0nm, respectively. The emission peak wavelength of the thin film sample obtained in Example 3 is 627.9nm, and the half-width is 45.1nm, respectively. The half-widths of both are lower than those of the sample obtained in Example 1, and the half-width of the sample obtained in Example 3 is the lowest. This indicates that adding an anti-solvent and changing the heat treatment temperature during crystal precipitation can both directionally regulate the half-width of the sample, and within a certain range, with the increase in the amount of anti-solvent added or the increase in the heat treatment temperature, the half-width of the obtained sample shows a downward trend.
Claims
1. A method for preparing a high-light-efficiency pure red light quasi-two-dimensional perovskite film, characterized in that: The raw materials including phenylpropylamine iodide, cesium iodide and lead iodide are fully dispersed in a solvent, and then a crown ether solution is added to obtain a thin film precursor solution, and then the thin film precursor solution is placed on a clean substrate to perform crystal precipitation and heat treatment in sequence to obtain; The stoichiometric ratio of the phenylpropylammonium iodide, cesium iodide and lead iodide is 2:1-2:2; the mass molar ratio of the crown ether solution to the phenylpropylammonium iodide is 1:0.8-1.2 g / mol based on the mass of the solute; An anti-solvent is added during the crystal precipitation process; the anti-solvent is at least one of chlorobenzene, benzene, methanol and dichloromethane; the volume ratio of the anti-solvent to the precursor solution is 1-3:1-4; The chemical formula of the two-dimensional perovskite film is PPA2CsPb2I7, where PPA=C9H 14 N.
2. The method for preparing a high-light-efficiency pure red light quasi-two-dimensional perovskite film according to claim 1, characterized in that: The solvent is at least one of N,N-dimethylformamide, dimethyl sulfoxide and acetonitrile; the concentration of iodide in the film precursor solution is 0.01-0.08 mol / L.
3. The method for preparing a high-light-efficiency pure red light quasi-two-dimensional perovskite film according to claim 1, characterized in that: The concentration of the crown ether solution is 5-20 mg / L; the crown ether solution is at least one of 18-crown ether-6 solution, 15-crown ether-5 solution and dicyclohexane-18-crown ether-6.
4. The method for preparing a high-light-efficiency pure red-light quasi-two-dimensional perovskite film according to claim 1, characterized in that: The cleaning process of the clean substrate is: ultrasonically cleaning the substrate with acetone, isopropanol, detergent, deionized water, acetone and isopropanol in sequence, then blowing dry the surface liquid phase on the substrate with nitrogen, and then drying at 40-80°C until completely dry.
5. The method for preparing a high-light-efficiency pure red-light quasi-two-dimensional perovskite film according to claim 1, characterized in that: Before the crystals are precipitated, the precursor solution and the clean substrate need to be preheated, and the conditions are: the preheating temperature is 60-120° C. and the time is 2-10 minutes.
6. The method for preparing a high-light-efficiency pure red-light quasi-two-dimensional perovskite film according to claim 1, characterized in that: The conditions for crystal precipitation are: temperature of 80-120° C., time of 1-5 min; the conditions for heat treatment are: temperature of 80-120° C., time of 15-30 min.
7. Application of the perovskite film obtained by the preparation method according to any one of claims 1 to 6, characterized in that: Used to prepare fluorescent anti-counterfeiting films.
